Exploring the Opportunities and Obstacles of Implementing Artificial Intelligence in Accounting and Auditing - Sakhno, Liudmyla; Сахно, Людмила Анатоліївна; Tkal, Yarmila; Ткаль, Ярміла Сергіївна; Sushko, Dmytro; Ocheretko, Larysa; Очеретько, Лариса Михайлівна; Shevchenko, Yevhen (My University, 2025)
EN: Introduction: Artificial intelligence technologies are being introduced into the economic sector due to the possibilities of automating processes. However, conservative views on using the latest technologies characterise accounting and auditing. This is because there is a risk of errors and confidential data leakage. Nevertheless, artificial intelligence is gradually being introduced into financial accounting and auditing, and today it is indispensable for some processes. Objectives: Our study aimed to determine the level of implementation of artificial intelligence technologies in accounting and auditing based on the survey results and identify the main factors influencing the level of artificial intelligence application in practice. Methods: To achieve this goal, the following methods were used: analysis, synthesis, induction, systematisation, and a survey of 947 respondents, including business people, business consultants, accountants, and auditors. Results: The survey results indicated a high level of use of artificial intelligence among business consultants and auditors, and the types of artificial intelligence were dominated by expert systems, machine learning, and customer support. At the same time, they identified a low level of use of complex systems, such as neural networks, blockchain technologies, and hybrid systems, against the background of low awareness among accountants and business people, accountants' fear of losing their jobs, and entrepreneurs' distrust of data protection and the potential for errors when using artificial intelligence. Conclusions: Thus, it is advisable to train accountants to help them adapt their professional activities to the current requirements of society and to encourage auditors and business consultants to advise entrepreneurs. /// UA: Вступ: Технології штучного інтелекту впроваджуються в сектор економіки завдяки можливостям автоматизації процесів. Однак консервативні погляди на використання новітніх технологій характеризують бухгалтерський облік і аудит. Це пов'язано з тим, що існує ризик помилок і витоку конфіденційних даних. Тим не менш, штучний інтелект поступово впроваджується у фінансовий облік та аудит, і сьогодні він незамінний для деяких процесів. Мета: Метою нашого дослідження було визначення рівня впровадження технологій штучного інтелекту в бухгалтерський облік і аудит за результатами опитування та виявлення основних факторів, що впливають на рівень застосування штучного інтелекту на практиці. Методи: Для досягнення поставленої мети були використані такі методи: аналіз, синтез, індукція, систематизація, а також опитування 947 респондентів, серед яких бізнесмени, бізнес-консультанти, бухгалтери та аудитори. Результати: Результати опитування засвідчили високий рівень використання штучного інтелекту серед бізнес-консультантів та аудиторів, а серед видів штучного інтелекту переважали експертні системи, машинне навчання та клієнтська підтримка. Водночас вони виявили низький рівень використання складних систем, таких як нейронні мережі, технології блокчейн та гібридні системи, на тлі низької обізнаності серед бухгалтерів та бізнесменів, страху бухгалтерів втратити роботу, а також недовіри підприємців до захисту даних та потенційної можливості помилок при використанні штучного інтелекту. Висновки: Таким чином, доцільно проводити навчання бухгалтерів, які б допомагали їм адаптувати свою професійну діяльність до сучасних вимог суспільства та заохочували аудиторів і бізнес-консультантів до консультування підприємців.
Вивчення можливостей та перешкод впровадження штучного інтелекту в бухгалтерський облік та аудит
Keywords: surveys; business consultants; accountants; auditors; entrepreneurs; expert systems; machine learning; autonomous robotic systems; neural networks; blockchain; technologies; hybrid systems; cybersecurity; опитування; бізнес-консультанти; бухгалтери; аудитори; підприємці; експертні системи; машинне навчання; автономні роботизовані системи; нейронні мережі; блокчейн технології; гібридні системи; кібербезпека